Salusin-alpha and -beta expression in heart and aorta with and without metabolic syndrome - Aydin, S.; Aydin, S. (Taylor & Francis Ltd, 2014)
Metabolic syndrome (MetS) is a major health problem throughout the world. The role of salusins has not been investigated in heart and aortic tissues under MetS conditions. We examined the distribution of salusin alpha (sal-alpha) and salusin beta (sal-beta) immunoreactivity in heart and aortic tissues and measured circulating salusin concentrations, glucose, insulin, triglycerides, free fatty acids, uric acid, and total cholesterol in Sprague-Dawley rats with and without MetS. Lipid, glucose, insulin and uric acid levels were determined using an autoanalyzer. Serum and tissue salusin levels were measured using ELISA. The expressions of salusins in the heart and aorta tissues were determined using immunohistochemical methods. Serum high density lipoprotein cholesterol (HDL-C), sal-alpha and sal-beta concentrations were significantly lower in the MetS group than in the control group. Low density lipoprotein cholesterol (LDL-C), very low density lipoprotein cholesterol (VLDL-C), total cholesterol, glucose, uric acid and insulin concentrations were higher in the MetS group than in the control group. Sal-alpha and sal-beta were synthesized locally in the fibroblasts and smooth muscle cells of the media of the aorta and in the muscle cells of the heart. Local synthesis of sal-alpha and sal-beta was decreased with MetS. Our findings indicate that decreased serum concentrations of salusins and HDL-C and increased uric acid, glucose and triglyceride concentrations may be indicators of MetS and could play a role in the development of cardiovascular disease.
Keywords: aorta; heart; fructose; metabolic syndrome; salusins